Profitability, Liquidity, and Capital Structure: An Analysis of Food and Beverage Companies in Indonesia: Profitabilitas, Likuiditas, dan Struktur Modal: Analisis Perusahaan Makanan dan Minuman di Indonesia - Wahyu Dwi Pangestining Tiyas; Nurasik Nurasik (Academia Open, 2022)
This study aims to examine the relationship between profitability, liquidity, and capital structure in the food and beverage sub-sector listed on the Indonesia Stock Exchange from 2017 to 2019. Through quantitative analysis, a purposive sample of 12 companies was selected, and data from annual reports were collected. The study utilized the IBM SPSS Statistics 25 program to analyze the data. The findings reveal that profitability has a positive but insignificant impact on capital structure, while liquidity demonstrates a positive and significant effect on capital structure. These results highlight the importance of managing liquidity effectively and optimizing operations to maintain favorable capital structure decisions. The implications of this study contribute to the understanding of financial management strategies within the food and beverage industry, aiding companies in making informed decisions to enhance profitability and meet short-term obligations. Highlights: Profitability and Liquidity: The study examines the relationship between profitability and liquidity in the context of capital structure decisions in food and beverage companies in Indonesia. Impact on Capital Structure: The analysis reveals the influence of profitability and liquidity on the capital structure of the selected companies, providing insights into the financial management strategies within the industry. Implications for Decision Making: The findings emphasize the significance of effectively managing liquidity and optimizing operations to maintain a favorable capital structure, aiding companies in maximizing profits and meeting short-term obligations. Keywords: Profitability, Liquidity, Capital Structure, Food and Beverage Companies, Indonesia.